A Study of Core Competencies for Supporting Roles in Engagement and Impact Assessment in Australia. Issue 2 (3rd April 2018) - Nicholson, James; Howard, Katherine
ABSTRACT: In 2018, Australia will include, for the first time, an engagement and impact (EI) assessment exercise as a companion to the Excellence in Research for Australia (ERA) national framework. The research underpinning this paper sought to identify the core competencies that are crucial to supporting roles within emerging impact and engagement expectations. A content analysis of research support position descriptions and job advertisements from the UK and Australia was conducted and these were mapped to current industry skill audits for library and information science (LIS) professionals. Also discussed are the current knowledge and skills of LIS professionals and what additional competencies they may need to acquire or develop if they are to contribute to institutions and researchers meeting the requirements of an EI assessment exercise. The hard skills required by both UK and Australian EI support roles are aligned to those endorsed and promoted by the LIS industry and are reflected in the Australian Library and Information skills templates. The study points to the viability of using current academic library networks and LIS professionals to meet the demands of future EI assessment in Australia.